DIPLOMASI EKONOMI INDONESIA DALAM MERAIH LEGALITAS EKSPOR PRODUK KAYU DI PASAR UNI EROPA TAHUN 2013-2016 - Laras Indah Nawangsih (2021)
The initial implementation of the EU Timber Regulation had caused a decline in the value of Indonesian wood product exports, this was due to the renewal of the concept of timber legality against forestry law in Indonesia which had been adapted to EU state regulations for Indonesian wood product entrepreneurs. Indonesia is required for its wood products to obtain a Forest Law Enforcement Governance and Trade (FLEGT) license, otherwise wood products from Indonesia will be subject to due diligence which will cost more or could be refused entry into the EU. To overcome these problems, Indonesia is required to conduct economic diplomacy with the EU. This study was conducted to analyze the efforts of Indonesia's economic diplomacy in achieving the legality of exporting wood products in the EU market. The method used is descriptive qualitative which explains more deeply about the forms of Indonesia's economic diplomacy efforts with the EU. This study uses the concept of economic diplomacy in analyzing Indonesia's efforts to obtain the legality of exporting wood products in the EU market. And the concept of national interest analyzes Indonesia's economic interests in economic diplomacy efforts carried out against the EU. Based on this research, there are implementations in Indonesia's economic diplomacy efforts to the European Union in achieving the legality of exporting Indonesian wood products, namely by developing and promoting SVLK with the European Union, Joint Working Group (JWG), Joint Expert Meeting (JEM), and Joint Implementation Committee (JIC), as well as the meeting between the President of Indonesia and the President of the European Commission is considered as a form of economic diplomacy carried out by Indonesia in achieving the legality of exporting wood products.